Topic of Apriorism in Modern Discussions of the Evolution of Consciousness - Liakh, V. V. (Anthropological Measurements of Philosophical Research, 2024)
Purpose. The article aims to: 1) to determine the place and role of a priori topoi of knowledge in the overall process of evolution of human consciousness, to clarify the relationship between innate and acquired human abilities; 2) to determine the creative potential of a priori and acquired human abilities on the basis of the evolutionary approach; 3) to clarify the basic intentions of a person which allowed him or her to reach a new level of adaptive behaviour. Theoretical basis. The article investigates the genesis and significance of the idea of a priori in the traditional theory of knowledge and its modern implications in the evolutionary theory of consciousness. The evolutionary approach allows us to rethink a fairly wide range of things that fall under the definition of a priori: from analytics, normativity, various attitudes of consciousness to human behavioural reactions. In the course of analysing Kant’s apriorism, which he used to justify the possibility of theoretical sciences, an attempt is made to determine the nature of a priori in the context of the evolutionary theory of consciousness. Although the idea of a priori was criticised by both Kant’s opponents (based on historical experience) and his followers (who opposed the formalism of a priori knowledge), the evolutionary theory of consciousness played a special role in this criticism and further development of this topic, contributing to a more detailed consideration of the genesis of the so-called a priori forms. Ultimately, through a combination of different forms of learning and a set of socio-cultural forms of mastering the world, man has managed to gain access to "potential intelligence" and a new "space for creation". Originality. The article substantiates the thesis that the evolutionary theory of consciousness allows explaining both the genesis of the a priori sphere and determining the mechanism of action of artificial formations or the achievements of human civilisation. Since people have gained the ability to generate and test hypotheses about reality instead of directly dealing with specific threats, the likelihood of wrong decisions and false preferences has arisen and is constantly growing. Therefore, in general, we have an urgent need for a double reflection – both on the limits of the application of a priori forms of knowledge and on the intentional attitudes of the human habitus. Drawing on the achievements of the evolutionary theory of consciousness, the author points to the possibility of a much broader approach to the problem of the a priori, which distinguishes not only different forms of knowledge, but also attitudes, biases, and intentions. In other words, the epistemological a priori is only a subdivision of the general sphere of innate and acquired human abilities. Hence, it can be argued that basic intentionality is also a kind of a priori, but it is widespread both in the field of ethics and in human behaviour. Conclusions. Based on Darwin’s ideas of natural selection, research in ethology, anthropology, neuroscience data, modern ideas about consciousness, etc., representatives of the evolutionary theory of consciousness proposed a more detailed approach to the study of the a priori. On the one hand, the belief in the apodictic reliability of a priori forms was undermined, and on the other hand, the complex nature of those forms of knowledge that Kant considered a priori was revealed. Ultimately, the idea of a priori leads us to questions about people’s ability to learn, to formulate tasks, hypotheses, theories, etc. In particular, the evolutionary theory of consciousness allows us to look at human cognitive abilities from the perspective of adaptation to environmental challenges.